STUDI EKSPERIMENTAL PROSES HARDENABILITY BAJA AISI 4340 PADA TEMPERATUR 900 O C, 1100 O C, 1400 O C DITINJAU TERHADAP HASIL UJI JOMINY TEST JURUSAN TEKNIK MESIN UNIVERSITAS TUJUH BELAS AGUSTUS 1945 SURABAYA - ., Ismail; Imanda, Herman (MEKANIKA: Jurnal Teknik Mesin, 2015)
Experimental Study Process hardenability Steel Aisi 4340 At temperatures of 900 Oc, 1100 c SeenOn Test Results Jominy Test, this research aims to data requirements thesis Department of Mechanical EngineeringUniversity August 17, 1945 Surabaya, Hardenability is the ability of the steel to be hardened to form martensite.Hardenability describe it hardening (depth of hardening) obtained by hardening, usually expressed by a distance ofa point below the surface where the structure consists of 50% martensite (presumed that occurs when a martensitichardening as much as 50%). A steel is said to have a high hardenabiliti if it shows thick steel hardening (depth ofhardening) were large or may harden the entire cross-section of an object large enough. To measure hardenabilition AISI 4340 steel by Jominy way. Testing hardenabiliti manner called Jominy end quench hardenability testbecause the test specimen is used berbentu cylindrical trunk diameter of 1 "(25 mm) long 4" (100 mm) which iscooled at one end. For this test use tool with a hole where the specimen is at its peak. Just below the specimencontained a nozzle diameter of 1 "(12.5 mm) for spraying cooling water to the height emission-free 2.5" (65 mm).Among the specimens with a nozzle mounted plate barrier that can be opened quickly shortly after the specimen isplaced in the holder hole. From the results of this test to obtain violence on AISI 4340 steel is higher than thestrength before doing the testing process.The test rod is heated at tempratur austenisasi for 30-35 minutes. Furnace atmosphere should be kept neutral inorder to avoid the formation of slag and carburizing. After the testing process Jominy This test is continuedkesebuah Rockwell testing process and testing of microstructure (Metallography), to obtain a data for theobservation process.Keywords: Process hardenability Steel Aisi 4340 Against Jominy Test Results Test